Pengalaman Lansia Dalam Melakukan Personal Hygiene Di Lingkungan Banjar Lebih Duur Kaje Gianyar - I Komang Ranandika; I Komang Sukraandini; Ni Luh Gede Puspita Yanti (Universitas Baiturrahim, 2020)
Health problems in the elderly were commonly caused by their gradual physiological changes. These physiological changes decrease their ability in doing their activity in daily living, one of them is personal hygiene. This study aimed to know the elderlies' experience in conducting personal hygiene in Banjar Duur Kaje Gianyar. This was a qualitative study using a descriptive phenomenology approach done in 2019. Four elderlies who met the inclusion criteria involved in this study. Interview and field notes were used to obtain the data. The data analysis using Colaizzi Method showed that there were four main themes on this study: (1) personal hygiene done by maintaining a healthy and clean body, (2) personal hygiene technique to keep the body clean: bathing, teeth brushing and using clean clothes, (3) hindrances in conducting personal hygiene, namely physiological factor and family support, and (4) overcoming those hindrances by doing personal hygiene according to the individual ability. We suggest the health care facilities and participant's families providing adequate physiological and psychological support for the elderly in conducting personal hygiene.